Synthesis and Structure of Novel A2BO5 Compounds Containing A = Y, Yb, Gd, Sm, and La and B = Zr, Ti, and Sn. (20th February 2018) - Newman, R.; Aughterson, R.D.; Lumpkin, G.R.
Abstract : With the aim of creating novel ceramics for applications in nuclear materials with high radiation tolerance, multiple samples with A-B-O stoichiometries ranging from 215 to 227 were synthesized and characterized by a combination of SEM, XRD, and TEM methods. Single-phase defect-fluorite-type compounds with A = Sm or Yb and B = Ti, Zr, and/or Sn are reported; whereas, pyrochlore structured compounds and lanthanide sesquioxide phases were found as major phases in numerous samples. A series of Y-b-Sn-O samples was successfully prepared as nearly single phase or single phase materials. These are essentially defect fluorites with extra weak peaks, most likely due to X-ray scattering from oxygen or oxygen and metal cations. We describe some interesting TEM data and describe selected area diffraction patterns with complex modulations.